2021
DOI: 10.1177/14644207211002763
|View full text |Cite
|
Sign up to set email alerts
|

Fracture energy assessment of adhesives – Part I: Is GIC an adhesive property? A neural network analysis

Abstract: Different joint types and geometries have been considered to measure the fracture toughness ( Gc) of adhesives. However, results show that, sometimes, the obtained Gc values for the same adhesives are not similar in different reports. Several factors including the joints geometry, material properties of the substrate, and also the test conditions influence the obtained results. This study is conducted to find a logical connection between these factors and to find their influences on the obtained mode I fractur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 40 publications
0
7
0
1
Order By: Relevance
“…However, recent studies by Akhavan-Safar et al [ 3 ], for mode I specimens, and Delzendehrooy et al [ 4 ], for mode II loading, have shown otherwise. G C might not be fully independent of the geometry and mechanical characteristics of the specimen.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies by Akhavan-Safar et al [ 3 ], for mode I specimens, and Delzendehrooy et al [ 4 ], for mode II loading, have shown otherwise. G C might not be fully independent of the geometry and mechanical characteristics of the specimen.…”
Section: Introductionmentioning
confidence: 99%
“…One of the fundamental issues for fracture analysis in adhesive joints is the concept of fracture energies [7][8][9][10][11]. Previous scientists proposed double cantilever beam (DCB) specimens with similar substrates for calculation of the mode I fracture energy of adhesive [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6] One of the fundamental issues for fracture analysis in adhesive joints is the concept of fracture energies. [7][8][9][10][11] Previous scientists proposed double cantilever beam (DCB) specimens with similar substrates for calculation of the mode I fracture energy of adhesive. 12,13 The difference in the material substrate fatigue and fracture behaviour of adhesive joints made from dissimilar adherends is more complex in comparison to adhesive joints made from similar adherends.…”
Section: Introductionmentioning
confidence: 99%
“…The fracture toughness is an important material property that must be taken into account when studying an adhesive's performance 14,15 . The effect of aging on this property has also been investigated in multiple researches.…”
Section: Introductionmentioning
confidence: 99%
“…The fracture toughness is an important material property that must be taken into account when studying an adhesive's performance. 14,15 The effect of aging on this property has also been investigated in multiple researches. Sugiman et al 16 studied the effect of aging on the mode II fracture toughness, concluding it increases on a first stage until the water content on the adhesive reaches 1.8% and, after that, it starts decreasing.…”
mentioning
confidence: 99%